Lund University Biological Museum - Zoological collections (MZLU) - Jonas Ekström (Lund University, 2010)
This database contains information on birds, mammals, reptiles, amphibians and invertebrates, except insects, from the Zoological Collections in the Museum of Biology of Lund, Sweden.
Keywords: Specimen; Occurrence; Occurrence; Specimen; OCCURRENCE; Biological Sciences; Biologi